Pendidikan Ilmu Humaniora dalam Al-Qur’an dan Hadist - Heni Susanti; Mahmudi (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Humanities education is one of the Islamic education that aims to straighten the way of thinking of society to be more humane, cultured and civilized. In humanities education, humans are expected to be more moral, social and civilized. Based on Islamic education sourced from the al-qur’an and hadith, this research was made in order to find out the education of the humanities in the al-qur’an and hadith. The method used is qualitative, with the type of literature review. From the results of the research that has been obtained, it can be said that humanities education is a science that can elevate humans to be more humane. In the al-qur'an and hadith, it is revealed that in establishing human life, it must be carried out by cultivating a meek attitude, not hard-hearted and not oppressing or degrading each other, because the position of every human being is the same.